Fascin is a potential biomarker for early-stage oesophageal squamous cell carcinoma. Issue 9 (8th March 2006) - Zhang, H; Xu, L; Xiao, D; Xie, J; Zeng, H; Cai, W; Niu, Y; Yang, Z; Shen, Z; Li, E
Abstract : Background: Fascin, an actin-binding protein, is usually expressed at a low level in normal epithelium, but is markedly up regulated in several types of carcinomas. Reports on fascin expression in oesophageal squamous cell carcinoma (ESCC) and precancerous lesions remain rare. Aim: To show the roles of fascin in the progression from normal epithelium to invasive ESCC. Methods: Fascin expression in 102 sections embedded in paraffin wax, including samples of normal mucosa (n = 20), dysplasia (n = 10), ESCC (n = 62) and special sections (n = 10) of a full-length mucosa layer from the distant margin to the cancer focus of the excised oesophagus, and 49 fresh specimens of ESCC was analysed by immunohistochemistry, western blot and real-time reverse transcription-polymerase chain reaction. Fascin expression in ESCC cell lines was also investigated. Results: In the immunohistochemical study, the positive rate of fascin was significantly higher in the tumour tissue than in the normal epithelium (p = 0.020), but no significant difference was shown between ESCC and dysplasia (p = 1.000). Immunostaining for fascin was only apparent in the basal layer of the normal epithelium. However, in the dysplasia, positive staining was observed in most of the heterogeneous cells from the basal layer to the granular layer of the epithelium. Fascin expression was seen to increase progressively from the normal epithelium to invasive ESCC. Up regulation of fascin was observed in 87.76% (43/49) and 77.55% (38/49) of the specimens, respectively, using western blot and real-time reverse transcription-polymerase chain reaction assays; 80% (4/5) of ESCC cell lines also expressed fascin at a high level. Furthermore, overexpression of fascin was markedly correlated with cell proliferation and lymph node metastasis. Conclusions: These findings suggested that fascin was associated with the transformation and development of ESCC and implicated the potential of fascin as a novel biomarker that would allow the tumour to be identified at an early stage in high-risk individuals.